The new synonymy of Horikawaea with Cryptogonium and a proposal of Pseudocryptogonium, gen. nov. (Musci, Pterobryaceae) - Akiyama, Hiroyuki; Tan, Benito C. (Phytotaxa, 2013)
Male organs and mature sporophytes of a calciphilous moss previously known as Horikawaea dubia are newly reported and described in detail based on a single specimen collected in Guangxi Province, southern China. Sporophytic features, such as the immersed and cylindrical capsule on a very short seta (ca. 1.2 mm long) and reduced peristome with 16 smooth and almost linear exostome teeth, as well as the gametophytic resemblance to Cryptogonium phyllogonioides in having complanate foliation, highly differentiated alar region of the stem and branch leaves, and more or less cucullate leaf apices, suggest a new synonymy of Horikawaea in Cryptogonium. Two new combinations, namely, C. dubia (Tixier) H.Akiyama & B.C.Tan comb. nov. and C. nitida (Nog.) H.Akiyama & B.C.Tan comb. nov. are made. Additionally, Pseudocryptogonium H.Akiyama & B.C.Tan gen. nov. is proposed to accommodate Horikawaea tjibodensis (syn. H. redfearnii).